STRUKTUR VEGETASI MANGROVE DI KAMPUNG NIPAH DESA SEI NAGALAWAN KECAMATAN PERBAUNGAN SERDANG BEDAGAI PROVINSI SUMATERA UTARA Vegetation Structure of Mangrove in, Kampung Nipah, Sei Nagalawan Village, District of Perbaungan, Serdang Bedagai, Sumatera Utara - Sari Marina Saragi; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Mangrove forest is a plant species whose life is still affected by sea tides. Mangrove forest is also a habitat of aquatic biota. In Kampung Nipah the utilization of Mangrove Forest is utilized as marine tourism. Utilization of mangrove forest that is not environmentally friendly is feared will threaten the preservation of mangrove forest ecosystem. The purpose of this research is to know the composition of mangrove species and mangrove vegetation structure which is currently viewed from Index of Density, Domination, Frequency, Importance Value Index, Diversity Index, and Mangrove Sharpness Index and Mangrove environmental condition in Kampung Nipah at Sei Nagalawan Village. This research was conducted for two months from December 2016 until January 2017. The method used to determine the location of sampling using Purposive Sampling at 3 stations. The structure of mangrove vegetation in stations I and II has a very dense density, density at station III is rarely.Keywords: Community Structure, Mangrove Density, Mangrove Utilization, Serdang Bedagai